The THE INFLUENCE OF COCOMELON CHANNEL IN ENHANCING ENGLISH SKILLS AT EARLY CHILDHOOD - Fitranti , Nasywa Salsabila (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
This study investigates the influence of the Cocomelon YouTube channel in enhancing English language skills in early childhood. With the rapid advancement of technology, particularly the development of new media such as social media and online platforms like YouTube, children are increasingly exposed to digital content from a young age. YouTube, being a popular online platform, offers a plenty of educational and entertaining content, including channels like Cocomelon, which cater specifically to children. The research explores the impact of Cocomelon as a medium for learning English vocabulary among children aged 4-6 years old. Utilizing a descriptive qualitative method with a literature review approach, the study examines how children engage with the channel's content and its effects on their English language skills. Data collection techniques involve interviews, observations, and documentation, with children aged 4-6 as the primary subjects. Findings suggest that Cocomelon, with its engaging animations, songs, and stories, significantly contributes to children's English language acquisition. The repetitive use of English vocabulary in various contexts, coupled with captivating visuals and melodies, facilitates vocabulary retention and comprehension. Moreover, the channel's content fosters children's motivation and enthusiasm for learning English, as observed through their active engagement with the videos. The study underscores the importance of technology integration in education, particularly in early childhood, and highlights YouTube as a valuable tool for language learning. By leveraging platforms like Cocomelon, educators and parents can create an immersive and enjoyable learning environment conducive to children's language development. Overall, the research concludes that Cocomelon's YouTube channel has a positive impact on early childhood English language skills, offering a fun and effective medium for vocabulary acquisition. However, it emphasizes the need for parental guidance and supplementary learning activities to maximize the channel's educational benefits.